The Relationship Between Informational Support And Emotional Support On The Quality Of Life Of Pulmonary TB Patients At The Puskesmas Kampung Pajak Labuhan Batu Utara - Naibaho , Eka Nugraha V.; Marpaung, Nazriana; Silaban, Nataria Yanti; Siburian , Christine Handayani (SEAN Institute, 2023)
Family is the main support system in maintaining health. The support provided by the family is the most important ingredient in helping individuals solve problems. Family support will also increase self-confidence and motivation to face problems and increase life satisfaction. The purpose of the study was to determine the relationship between informational support and emotional support on the quality of life of Pulmonary TB patients at the Puskesmas Kampung Pajak Labuhan Batu Utara. The research method uses quantitative research with a Cross Sectional approach. The research was carried out at the Puskesmas Kampung Pajak Labuhan Batu Utara in June-July 2021. The study population was Pulmonary TB patients who came to the Puskesmas Kampung Pajak Labuhan Batu Utara as many as 64 people, Sampling technique using Total Sampling, the number of research samples was 64 people who came to the Puskesmas Kampung Pajak Labuhan Batu Utara. Univariate and bivariate, bivariate data analysis techniques were carried out using the Chi Square Test assisted by SPSS 22 software. The results of the study there was a relationship of informational support with quality of life with a significant value of 0.002<0.05, there was a relationship of emotional support with quality of life with a significant value of 0.004<0.05. Suggestions become education to patients to involve families in helping patients to improve health through family support to patients.